The Book Review of “Egyptian Literature from the Establishment of the Ayyubi State until French Campaign” - Sadq Askari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Critical review of scientific production reveals the weaknesses of the works of the previous works, so we can avoid the shortcomings and strengthen our works.. Therefore, it can be said that achieving the optimum perfection in the development of academic resources is possible only after reviews. The present paper aims to review  the book entitled "Egyptian Literature from the Establishment of the Ayyubi State to the Advent of the French Campaign ",written by Abdul Latif Hamza, and  published in 2000 by the publication  "Egyptian General Institute Forum for the Books" in 293 pages.The results of the critique and review of this book show that this book, despite some strengths such as observance of the rules of writing, the coherence and logical setting of the sections and chapters; unfortunately, it has many defects in the field of form and content. The most important drawbacks of this work include lack of registration of bibliography references and shortages, lack of introduction and closure for the sections and chapters, verbal errors due to non-observance of rules, lexical errors due to non-observance of the rules of conduct, interpretive errors and misunderstandings due to the inappropriate use of words and combinations. But the main drawbacks of the content in this book are repetition of the subject, surreptitious review due to the wide scope of the subject, reliance on compilation and accumulation as a result of the lack of analysis and innovation. It is hoped that the results of this brief review would be useful for the writer and other scholars, and would Lead to scientific promotion.